Memoirs, confessions and apologies: the last chapter of Byzantine autobiography. (August 2013) - Angold, Michael
Abstract : Two issues are addressed here: the status of Byzantine autobiography and the state of Byzantine literary culture in its last years. Autobiographical information was mostly a device used at all levels of Byzantine literature for immediacy, emphasis and to suggest personal involvement. It continued to function in this way in the last years of Byzantium, but there was also a degree of experimentation, as it extended its range into satire and comedy and, in the hands of Theodore Agallianos evolved from the rhetoric of apologia into fully-fledged autobiography.